(untitled) (Jurnal Kemanusiaan, 2017)
Accounting has a legitimate role in the globalised context in supporting concerns to protect and promote human rights through the concept of corporate transparency. Additionally, the language of human rights has entered the discourse of corporate accountability in the form of accounting disclosure on human rights. Hence, this paper attempts to investigate the adoption of voluntary disclosure on human rights among construction companies in Malaysia for the year 2010. The paper reviews the issues of human rights in Malaysia, the current human rights in corporations nowadays, accounting disclosure on human rights and, specifically human rights disclosure in the construction industry. Through the method of content analysis, this study has found that only 70% of the construction companies in Malaysia disclosed items on human rights which focus on occupational health and safety among employees. However, disclosure of other areas of human rights such as employee beliefs, harassment, freedom of association, and elimination of all forms of discrimination were performed by only 13% of the construction companies. The findings concluded that voluntary disclosure on human rights among construction companies in Malaysia are still at the initial stage.